Development of Flash Card Media to Improve Expressive Language Skills in Children with Motor Impediments - Rizki Ramadhana; Oom Sitti Homdijah; Riksma Nurahmi Rinalti Akhlan; Imas Diana Aprilia; Budi Susetyo (Universitas Muhammadiyah Enrekang, 2023)
The problems of children with motor disabilities who experience expressive language difficulties need to get the right solution so that these difficulties can be overcome and get learning services that suit their abilities and needs. Based on these problems the researcher developed Flash Card media which has a very important role to make it easier for children to perceive something. One of the difficulties in learning to read technically is because it is difficult to think abstractly, so the teacher can work around this by using media that is in accordance with the goals and material being taught. The way to overcome these problems is to develop learning media that are suitable for children's abilities. Media is needed to make it easier for children with motor impairments to learn. The method used is a descriptive qualitative approach.